2006
DOI: 10.1073/pnas.0605551103
|View full text |Cite
|
Sign up to set email alerts
|

Partially redundant functions of two SET-domain polycomb-group proteins in controlling initiation of seed development in Arabidopsis

Abstract: In Arabidopsis, a complex of Polycomb-group (PcG) proteins functions in the female gametophyte to control the initiation of seed development. Mutations in the PcG genes, including MEDEA (MEA) and FERTILIZATION-INDEPENDENT SEED 2 (FIS2), produce autonomous seeds where endosperm proliferation occurs in the absence of fertilization. By using a yeast two-hybrid screen, we identified MEA and a related protein, SWINGER (SWN), as SET-domain partners of FIS2. Localization data indicated that all three proteins are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 46 publications
7
107
0
Order By: Relevance
“…As a positive control, we hybridized ovule sections with a HISTONE4 (HIS4) antisense probe and observed its characteristic patchy expression pattern in actively dividing cells (Figures 3J and 3K) (Blein et al, 2008). Consistent with these results, MEA and FIS2, the other FIS genes specifically expressed in the central cell (Luo et al, 2000;Wang et al, 2006), do not affect seed coat development (Roszak and Köhler, 2011). We showed that fis2/+ unfertilized ovules do not undergo nucellus degeneration at 6 DAF (Supplemental Figure 5).…”
Section: Polycomb Proteins Repress the Degeneration Of The Nucellussupporting
confidence: 64%
See 1 more Smart Citation
“…As a positive control, we hybridized ovule sections with a HISTONE4 (HIS4) antisense probe and observed its characteristic patchy expression pattern in actively dividing cells (Figures 3J and 3K) (Blein et al, 2008). Consistent with these results, MEA and FIS2, the other FIS genes specifically expressed in the central cell (Luo et al, 2000;Wang et al, 2006), do not affect seed coat development (Roszak and Köhler, 2011). We showed that fis2/+ unfertilized ovules do not undergo nucellus degeneration at 6 DAF (Supplemental Figure 5).…”
Section: Polycomb Proteins Repress the Degeneration Of The Nucellussupporting
confidence: 64%
“…All four FIS genes, MEDEA (MEA), FIS2, FERTILIZATION INDEPENDENT ENDOSPERM (FIE), and MULTICOPY SUPPRESSOR OF IRA1 (MSI1), are expressed in the ovule central cell and repress its division before fertilization Kiyosue et al, 1999;Luo et al, 1999;Ohad et al, 1999;Yadegari et al, 2000;Hennig et al, 2003;Köhler et al, 2003;Guitton et al, 2004;Wang et al, 2006). By contrast, only FIE and MSI1 are also expressed in sporophytic tissues and repress seed coat development (Ohad et al, 1999;Hennig et al, 2003;Köhler et al, 2003;Roszak and Köhler, 2011).…”
Section: Polycomb Proteins Repress the Degeneration Of The Nucellusmentioning
confidence: 99%
“…5), suggesting that CLF competes with MEA in the formation of PRC2 complexes. This is consistent with the fact that both CLF and MEA are able to interact in vitro with the same Su(z) homologs, including FIS2, that are expressed in endosperm (18,36). So, the question arises, how is CLF and MEA function separated during endosperm development when their respective RNA expression patterns and ability to interact with PcG proteins overlap?…”
Section: Discussionsupporting
confidence: 51%
“…PcG proteins related to MEA (SWINGER and CURLY LEAF) and FIS2 (VERNALIZATION 2 and EM-BRYONIC FLOWER 2) are expressed in endosperm (http:// seedgenenetwork.net). These proteins can interchangeably form PRC2 complexes (36) and might provide redundant PRC2 functionality in a dme mutant background.…”
Section: Effects Of Paternal Met1 and Maternal Dme And Fie Mutations Onmentioning
confidence: 99%